Processing Of Red Gypsum Using Hyddrocyclone - Abd Jabar, Muhamad Hafizuddin (Universiti Sains Malaysia, 2022)
Red Gypsum (RG) is another potential waste material that can replace cement in cement production. Red gypsum (RG), also a reddish brown semi-solid mud is a waste generated from a sulphate process of ilmenite ore which is rich in titanium and iron to acquire titanium oxide. High iron content on gypsum inhibits the decomposition of the red gypsum (RG). The addition of iron can increase the quantity of the liquid phase and effect the decomposition of red gypsum. However, the excess liquid phase caused by the high iron content will wrap the gypsum and thus inhibits its decomposition as a binder in cement production. The characterization of RG such as physical and chemical properties are tested using standard laboratory standard. Testing including the measurement of particle size analysis and X-Ray Fluorescence (XRF) and some important properties including moisture content and specific gravity. So, ad addition of different type of acid on that physical processing can upgrade the Red Gypsum (RG) content and can produce information on the possibility in using of Red Gypsum (RG) on cement industry in conjunction with standard test for more complete information.